The Dual Capacity of Happiness at Work: A Systematic Narrative Review in the Hospitality Industry - Ita Juwitaningrum; Diah Zaleha Wyandini (Indonesian Journal of Tourism and Leisure, 2026)
This study aims to synthesize and examine existing research on happiness at work (HAW) within the hospitality industry. This paper identified how the construct is conceptualized, what organizational mechanisms shape it, and how it influences key organizational outcomes.  A systematic narrative review methodology was adopted, combining the structured transparency of systematic selection with the interpretive depth of narrative synthesis. Following PRISMA guidelines, a total of 15 peer-reviewed articles published between 2016 and 2025 were retrieved from Scopus, Taylor & Francis, and Emerald databases and analysed using thematic synthesis. HAW in hospitality operates not merely as an organizational endpoint but as a dual-capacity construct. The review further highlights that the specific conceptual lens through which HAW is approached determines which mechanisms are most effective and which outcomes are most likely to follow. The hospitality context also introduces industry-specific conditions that shape how happiness manifests and must be managed. Our article offers a more organizationally precise foundation by restricting its scope to workplace happiness, in contrast to prior review that incorporated broader well-being constructs.